2022
DOI: 10.17576/jsm-2022-5104-11
|View full text |Cite
|
Sign up to set email alerts
|

Phenethyl p-coumarate and N-phenethyl-p-coumaramide: Synthesis, Characterization, Docking Studies, and Anticancer Activity through P388 Cell

Abstract: Most p-coumaric acid derivatives and molecules containing phenethyl moiety have a potential in anticancer activity. Thus, combining a p-coumaroyl group and a phenethyl moiety in one compound will increase anticancer activity. The principal objective of this research was to incorporate p-coumaroyl and phenethyl moieties to form an ester, phenethyl p-coumarate (5), and an amide, N-phenethyl-p-coumaramide (6), then tested their anticancer activity using P388 leukemia murine cells. The characterization by FTIR met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The two most abundant compounds in the aromatic ginger essential oil were trans-ethyl-pmethoxycinnamate and trans-ethyl cinnamate [1][2]5]. Ethyl-p-methoxycinnamate and its derivatives had many benefits, including as anticancer [6][7][8], anti-inflammatory [9][10], anti-tuberculosis [11], anti-neoplastic [12], antimicrobe [13], and antidiabetic [14] agents. The study of K. galanga L. extract as an antidiabetic using the Gavage method every day for one month found that diabetic rats before and after treatment with K. galanga L. extract showed a significant difference in reducing the amount of blood glucose [15].…”
Section: ■ Introductionmentioning
confidence: 99%
“…The two most abundant compounds in the aromatic ginger essential oil were trans-ethyl-pmethoxycinnamate and trans-ethyl cinnamate [1][2]5]. Ethyl-p-methoxycinnamate and its derivatives had many benefits, including as anticancer [6][7][8], anti-inflammatory [9][10], anti-tuberculosis [11], anti-neoplastic [12], antimicrobe [13], and antidiabetic [14] agents. The study of K. galanga L. extract as an antidiabetic using the Gavage method every day for one month found that diabetic rats before and after treatment with K. galanga L. extract showed a significant difference in reducing the amount of blood glucose [15].…”
Section: ■ Introductionmentioning
confidence: 99%